Detection of aneuploidy using multiplex ligation–dependent probe amplification in fetal tissues from aborted pregnancies: Določanje anevploidij z metodo pomnoževanja od ligacije odvisnih prob v fetalnih tkivih splavkov - Zagradišnik, Boris; Stangler Herodež, Špela; Erjavec-Škerget, Alenka; Zagorac, Andreja; Kokalj-Vokač, Nadja (Acta Medico-Biotechnica, 2021)
Purpose: About 10-15% of all pregnancies terminate as spontaneous miscarriages. In the first trimester, ≈50% of spontaneous miscarriages are the result of chromosomal aberrations, mostly chromosomal aneuploidies. Cytogenetic analyses are used to confirm aneuploidy in failed pregnancies. Culture failure or poor-quality chromosomes are often problems in those cases. In such situations, methods that are independent of tissue culture are used, and we employed multiplex ligation-dependent probe amplification (MLPA). We determined if MLPA is an appropriate and compatible method compared with classical cytogenetic analyses on fetal tissues.Methods: All fetal samples received from spontaneous abortions were cultured, karyotyped (if possible) and genomic DNA extracted. MLPA analyses were undertaken using subtelomeric probe kits. Additionally, comparative genomic hybridization (CGH) was used to confirm aneuploidy detected by MLPA in cases of failed culture growth.Results: MLPA analyses confirmed an unbalanced chromosome abnormality identified by cytogenetic analyses in all cases in which tissue culture was successful, and provided data in cases of failed culture growth. Several common numeric chromosome aberrations were detected, as well as rare trisomies and other unbalanced chromosome rearrangements.Conclusions: MLPA analyses can provide information about the karyotype of a DNA sample if cytogenetic analyses are not possible because of a lack of viable cells or if only a small amount of genomic DNA is available. Th
Keywords: multiplex ligation–dependent probe amplification; numeric chromosome aberration; karyotype